1989
DOI: 10.1111/j.1365-2648.1989.tb01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching psychomotor skills in nursing: a randomized control trial

Abstract: Historically, McMaster University School of Nursing in Hamilton, Ontario, Canada has utilized self-directed learning methods to teach psychomotor nursing skills to undergraduate nursing students. Second year students, in their post-clinical evaluations indicated a desire for a structured laboratory setting to assist them in acquiring these skills. In response, faculty designed a randomized control trial to compare the effectiveness of teaching psychomotor skills in a structured laboratory setting with self-dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
1
7
0
3
Order By: Relevance
“…Many researchers have highlighted the use of clinical skills laboratories in nurse education (Gomez & Gomez 1987, Love et al. 1989, Jeffries et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers have highlighted the use of clinical skills laboratories in nurse education (Gomez & Gomez 1987, Love et al. 1989, Jeffries et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This multimodal approach involves the use of clinical skills laboratories, computer assisted learning (CAL), use of audio-visual (AV) equipment, elearning, didactic teaching and demonstration (Love et al 1989;Jeffries et al 2002;Bloomfield et al 2008;Bloomfield et al 2013). In contrast to Ireland, the UK Nursing and Midwifery Council (NMC) clearly outline essential skills clusters to guide educational and clinical staff (NMC 2010).…”
Section: )mentioning
confidence: 99%
“…10 Love et al found no difference in an undergraduate nursing school teaching psychomotor skills. 11 Beeson and Kring showed no difference in nursing knowledge and skill of blood pressure measurement between traditional lecture and videointeractive methods. 12 In 2001, Vidal et al also reported no difference in teaching methods in a Brazilian program to teach physicians and nurses newborn care.…”
Section: Discussionmentioning
confidence: 99%